2021
DOI: 10.21107/dinar.v7i2.11250
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Of Halal Value Chain In Business In Islamic Boarding Schools

Abstract: This study aims to determine the implementation of the halal value chain in the Islamic Boarding School business. In this article, the focus of the study is on the oyster mushroom business, starting from the process of cultivating oyster mushrooms to being processed food, and the sales process at the Nurul Amanah Islamic Boarding School, Basanah, Bangkalan.This type of study is a qualitative study with observational study methods. While the data collection methods were carried out through observation, intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Sayangnya di cabang ini kompetisi pasar dengan brand kompetitor lainnya berjalan ketat. Ini dibuktikan dengan omset penjualan Beberapa penelitian mengenai strategi peningkatan jumlah penjualan untuk bisnis pakaian antara lain penerapan strategi komunikasi pemasaran [3], [8], analisis strategi bisnis menggunakan SWOT [1], [9]- [11] dan penerapan metode value chain [12], [13]. Metode Value chain adalah salah satu metode analisis yang populer digunakan dalam kajian strategi bisnis.…”
Section: Pendahuluanunclassified
“…Sayangnya di cabang ini kompetisi pasar dengan brand kompetitor lainnya berjalan ketat. Ini dibuktikan dengan omset penjualan Beberapa penelitian mengenai strategi peningkatan jumlah penjualan untuk bisnis pakaian antara lain penerapan strategi komunikasi pemasaran [3], [8], analisis strategi bisnis menggunakan SWOT [1], [9]- [11] dan penerapan metode value chain [12], [13]. Metode Value chain adalah salah satu metode analisis yang populer digunakan dalam kajian strategi bisnis.…”
Section: Pendahuluanunclassified
“…Indonesian Muslims make up a significant portion of the world's Muslim population, accounting for 12.7% of all Muslims. Hence they become the largest 320 e-ISSN: develop optimally because of the traditional view that regards Pesantren only as a transmitter of knowledge and teachings of Islam (Dzikrulloh & Koib, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Annisa (2019) suggests the family culture in Pesantren might encourage the concept of a halal value chain as a standard for sharia-compliant production, distribution, or consumption activities. The Government Regulation of Indonesia Number 31, 2019, andLaw Number 33, 2014, as well as the list of halal and positive materials by LPPOM MUI, are the guideline from the input process, tools, and materials used to the distribution of the resulting product by Pesantren business unit (Dzikrulloh & Koib, 2020). Holding business of Pesantren is one of the three Pesantren independence development strategies (Habibussalam, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some research concluded that many MSMEs run a halal ecosystem. 19 Regarding the research which found that several Pesantren succeeded in implementing the halal value chain in the management of their business units 20 , the other also found that Pesantren cooperatives were able to revive the halal value chain in the Pesantren environment and implementing it well. 21 This is supported by the research which found that Pesantren could implement the halal value chain in their products well and meet JPH standards.…”
Section: Introductionmentioning
confidence: 99%